2023
DOI: 10.1021/acs.orglett.2c04198
|View full text |Cite
|
Sign up to set email alerts
|

B(C6F5)3-Catalyzed Diastereoselective and Divergent Reactions of Vinyldiazo Esters with Nitrones: Synthesis of Highly Functionalized Diazo Compounds

Abstract: Herein we report a mild, transition-metal-free, highly diastereoselective Lewis acid catalyzed methodology toward the synthesis of isoxazolidine-based diazo compounds from the reaction between vinyldiazo esters and nitrones. Interestingly, the isoxazolidine products were identified to have contrasting diastereoselectivity to previously reported metal-catalyzed reactions. Furthermore, the same catalyst can be used with enol diazo esters, prompting the formation of Mukaiyama–Mannich products. These diazo product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…[32][33][34][35] Tris(pentauorophenyl)borane [B(C 6 F 5 ) 3 ] is a wellestablished Lewis acid that has previously been shown to activate a wide range of substrates. Recently, we have shown that B(C 6 F 5 ) 3 can catalyse the Mukaiyama-Mannich addition of nitrones with silylenol diazo esters, 36 and we envisioned that we could similarly employ it to catalyse the nitro-Mannich reaction, providing an orthogonal method to existing procedures. Based on this premise, we decided to expand the applicability of the nitro-Mannich reaction by using nitrones as imine surrogates, and by investigating different silyl nitronates under Lewis acid catalysis conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35] Tris(pentauorophenyl)borane [B(C 6 F 5 ) 3 ] is a wellestablished Lewis acid that has previously been shown to activate a wide range of substrates. Recently, we have shown that B(C 6 F 5 ) 3 can catalyse the Mukaiyama-Mannich addition of nitrones with silylenol diazo esters, 36 and we envisioned that we could similarly employ it to catalyse the nitro-Mannich reaction, providing an orthogonal method to existing procedures. Based on this premise, we decided to expand the applicability of the nitro-Mannich reaction by using nitrones as imine surrogates, and by investigating different silyl nitronates under Lewis acid catalysis conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the observed [3+3]-annulation with nitronates differs from the reaction of vinyl diazoacetates with nitrones, which often proceeds via a [3+2]-pathway and subsequent carbene reactions (cf. path b) [ 63 , 64 , 65 , 66 ], while the respective [3+3]-pathway was rarely observed [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently we have identified that vinyl diazoesters showed divergent reactivity with borane catalysts in the presence of nitrones (Scheme 22). 45 By switching the diazo precursor and the reaction conditions (B(C6F5)3 loading and temperature), either isoxazolidines or Mukaiyama−Mannich addition products could be afforded in which the diazo functionality was untouched. A range of isoxazolidine and Mukaiyama−Mannich addition products were isolated in moderate to good yields and good diastereoselectivities was observed.…”
Section: Group Transfer Reactionsmentioning
confidence: 99%